Gender, Subjectivity, and Cultural Work: The Classical Music Profession - Scharff, Christina (Routledge, 2017)
What is it like to work as a classical musician today? How can we explain ongoing gender, racial, and class inequalities in the classical music profession? What happens when musicians become entrepreneurial and think of themselves as a product that needs to be sold and marketed? Gender, Subjectivity, and Cultural Work explores these and other questions by drawing on innovative, empirical research on the working lives of classical musicians in Germany and the UK. Indeed, Scharff examines a range of timely issues such as the gender, racial, and class inequalities that characterise the cultural and creative industries; the ways in which entrepreneurialism – as an ethos to work on and improve the self – is lived out; and the subjective experiences of precarious work in so-called ‘creative cities’. Thus, this book not only adds to our understanding of the working lives of artists and creatives, but also makes broader contributions by exploring how precarity, neoliberalism, and inequalities shape subjective experiences. Contributing to a range of contemporary debates around cultural work, Gender, Subjectivity, and Cultural Work will be of interest to scholars and students in the fields of Sociology, Gender and Cultural Studies.
Keywords: Music; Myriam; Social Science / General; Social Science / Sociology / General